Continuous Tubular Nanofibers of Vanadium Pentoxide by Electrospinning for Energy Storage Devices - Neeta L., Lala; Rajan, Jose; M. M., Yusoff; Seeram, Ramakrishna (Springer Netherlands, 2012)
Tubular nanofibers (TNFs) of vanadium pentoxide (V2O5) were synthesized by electrospinning technique using a single spinneret for the first time by controlling the properties of the precursor solution. A partially miscible polymeric solution of vanadium oxytrihydroxide [VO(OH)3] was produced by hydrolysis of vanadyl acetylacetonate in Poly(vinylpyrrolidone) (PVP). The phase-separated polymer solution formed the core of the electrospun fibers whereas the VO(OH)3 formed the shell; the core PVP has been removed by controlled heat treatment. The TNFs had an inner diameter ~60 nm and wall thickness ~±100 nm. The capacitive behavior of the V2O5 TNFs was studied using cyclic voltammetry and galvanostatic cycling techniques. The studies showed ideal stable supercapacitive characteristics in the electrospun V2O5 TNFs.